Dilatancy controlled spatiotemporal slip evolution of a sealed fault with spatial variations of the pore pressure - Hillers, Gregor; Miller, Stephen Andrew (My University, 2007)
A range of observations suggest the formation and maintenance of sealed and hence overpressured compartments in fluid-infiltrated fault zones. It is assumed that hydromechanical properties of regions with variable pore pressure states control the fault's stability and thus its characteristic response, that is, seismic or aseismic slip accumulation. We investigate in a systematic parameter space study the effects of spatial variations in pore pressure on spatiotemporal slip evolution along a hydraulically isolated fault plane. The 3-D continuum model is governed by rate-and-state friction and constitutive laws for porosity reduction. We show that the model response is sensitive to the degree of overpressurization and the efficiency of dilatant hardening mechanisms. Low pore pressures and small dilatancy effects result in unstable response types, whereas high pore pressures and large dilatant effects lead to stable and aseismic creep. Regions with an unstable response are shown to support most of the stresses accumulated during interseismic periods. Accelerated slip nucleates preferably in regions of low pore pressure. Statistical properties of model seismicity produce a wide range of event sizes for moderate and large earthquakes, in the case where dilatant mechanisms are inefficient. In case of efficient slip rate controlled porosity increase, less instabilities grow into large earthquakes. Final slip maps demonstrate the applicability of the chosen method to model seismicity controlled by frictional and hydraulic processes on a planar fault plane. The evolution of governing variables that depend on the pore pressure environment provide a conceptual basis for the interpretation of observed response characteristics.